2009
DOI: 10.1111/j.1460-2695.2009.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inclusion size on S‐N curve characteristics of high‐strength steels in the giga‐cycle fatigue regime

Abstract: A B S T R A C T Fatigue fracture of high-strength steels often occurs from small defect on the surface of a material or from non-metallic inclusion in the subsurface zone of a material. Under rotating bending loading, the S-N curve of high-strength steels consists of two curves corresponding to surface defect-induced fracture and internal inclusion-induced fracture. The surface defect-induced fracture occurs at high stress amplitude levels and low cycles. However, the subsurface inclusion-induced fracture occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…The area (II) of the region outside the initial site is larger than in the higher cycle failure case with N f =5.366x10 8 . The radial streaks for area (III) were more clear for N f =5.366x10 8 than for N f =3.089x10 5 , and the roughness of area (III) for N f =3.089x10 5 is larger than for N f =5.366x10 8 . This corresponds to faster crack propagation for lower cycle case with high stress levers.…”
Section: Fractographymentioning
confidence: 83%
See 1 more Smart Citation
“…The area (II) of the region outside the initial site is larger than in the higher cycle failure case with N f =5.366x10 8 . The radial streaks for area (III) were more clear for N f =5.366x10 8 than for N f =3.089x10 5 , and the roughness of area (III) for N f =3.089x10 5 is larger than for N f =5.366x10 8 . This corresponds to faster crack propagation for lower cycle case with high stress levers.…”
Section: Fractographymentioning
confidence: 83%
“…Gigacycle fatigue failures for high strength materials have become a serious industrial matter [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The conventional fatigue experiment with a load frequency of 10 Hz costs more than one thousand days to reach 10 9 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Mg 2 Si particles in the NZ have a larger size than the Fe-rich particles, because the Fe-rich particles exhibited multiple cracks, which is much more serious than that of Mg 2 Si particles [25]. Generally, the defect size is the crucial factor to control the fatigue strength in the VHCF range for high strength steel with non-metallic inclusion, and the fatigue crack initiated from the inclusion with maximum diameter [31,32]. In this test, the intergranular particles in the NZ are supposed to play similar roles as the inclusions in high strength steel for the similar failure mechanisms as presented in Fig.…”
Section: Fatigue Crack Initiation Behaviormentioning
confidence: 99%
“…It was established that the major part of fatigue life is spent during crack propagation, whereas the fraction of fatigue life spent during initiation is usually much smaller. In the 30 recent years, the industrial technology development has led to some machine components failures beyond 10 7 cycles, and consequently, the asymptote might not exist in some cases of S‐N curves of steels . Bathias et al suggested to ban the fatigue limit concept, and to replace it by fatigue strength for a considered number of cycles …”
Section: From High Cycle Fatigue (Hcf) To Very High Cycle Fatigue (Vhmentioning
confidence: 99%